Freedom of information to receive government information (Journal of the College of Basic Education, 2022)
Access to information is subject to ebbs and flows in any country; Is thatThe process of transformation has begun and it is no longer possible to tell citizens that knowledge is not worth itfor them.A new era of government transparency has begun. It became widely knownToday, the culture of secrecy that used to shape the way governments operate is at a stretchYears are no longer applicable in the global age of information and therefore ofIt is necessary for governments in the information age to provide information in order toSuccess.